Criteria for Determining the Alignment between the Content of TIMSS Science Items and Science and Social Studies Teaching Curriculum - Zorica P. Veinović; Jelena S. Jaranović; Milan S. Stančić; Olja S. Jovanović (University of Belgrade, Teacher Education Faculty, 2018)
Analysis of compatibility of tasks and syllabi of the participating countries represents one of the procedures, which provide comparison of results within the TIMSS study. Due to the fact that criteria for determination of this compatibility are not explicit, there is a question posed regarding the procedures, whether all the different countries approach this process in the same way and whether their results surely enable comparison of aspects of students between the countries and observing achievements of students in comparison to syllabi. This is why the aim of this paper is defining criteria that would enable accurate classification of TIMSS tasks from the field of natural sciences concerning the syllabi issues and those, which do not belong to syllabi. Based on the analysis of the current syllabi and educational standards of teaching natural and social sciences in the first cycle of primary education, we defined two kinds of criteria for tasks classification: incorporating the contents of the tasks into the syllabi contents and/or educational standards and compatibility of the contents of the tasks with the principle of homeland. Validity and quality of using these criteria were examined by classification of the published tasks from the TIMSS 2011 study. Compatibility between estimations of the authors of the paper and external expert concerning the sample of tasks was satisfactory. In the paper, we gave possibilities of defining general criteria that all the countries participants in the study would follow, and possibilities of the TIMSS study to be more prone to national particularities concerning the syllabi.